Пошаговое объяснение:
3 . z = r ( cosφ + i sinφ ) ;
a ) z = - i ; r = √( 0² + ( -1 )² ) = √ 1 = 1 ; φ = arctg( -1/0 ) = - π/2 ;
- i = cos(- π/2) + i sin(- π/2 ) ;
б ) z = 1/2 + i √3/2 ; r = √[ (1/2)² + ( √3 /2 )²] = 1 ; φ = arctg(√3/2 : 1/2 ) =π/3 ;
1/2 + i √3/2 = cos(π/3 ) + i sin(π/3 ) .
Пошаговое объяснение:
3 . z = r ( cosφ + i sinφ ) ;
a ) z = - i ; r = √( 0² + ( -1 )² ) = √ 1 = 1 ; φ = arctg( -1/0 ) = - π/2 ;
- i = cos(- π/2) + i sin(- π/2 ) ;
б ) z = 1/2 + i √3/2 ; r = √[ (1/2)² + ( √3 /2 )²] = 1 ; φ = arctg(√3/2 : 1/2 ) =π/3 ;
1/2 + i √3/2 = cos(π/3 ) + i sin(π/3 ) .